2017
DOI: 10.18553/jmcp.2017.23.6-b.s2
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Pimavanserin in the Management of Parkinson’s Disease Psychosis

Abstract: This project and manuscript was funded by ACADIA Pharmaceuticals and developed by Magellan Rx Management. Lopes and Farnum are employees of Magellan Rx Management. Kremens has received consulting/speaker fees from Teva Pharmaceuticals, UCB, Sunovion, Impax, Lundbeck, ACADIA, USWorldMeds, Merz, Acorda, Kyowa, Neurocrine, and GE Healthcare. Pagan reports consulting/speaker fees from Teva Nanoscience, AbbVie, Impax, ACADIA, Medtronic, USWorldMeds, Merz, and Cynapsus and research and educational grants from USWorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Although these four studies noted some adverse events such as somnolence, peripheral edema, urinary tract infection, falls, confusion, headache, and hallucinations, there was no significant difference between the two arms. According to the results, we found that pimavanserin may be adequate for use as a first-line treatment for PDPsy because it improves the psychotic symptoms without worsening motor function, which was in accordance with the conclusions and guidelines reported previously 10,15,41. Additionally pimavanserin provided robust proof for clinically significant efficacy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although these four studies noted some adverse events such as somnolence, peripheral edema, urinary tract infection, falls, confusion, headache, and hallucinations, there was no significant difference between the two arms. According to the results, we found that pimavanserin may be adequate for use as a first-line treatment for PDPsy because it improves the psychotic symptoms without worsening motor function, which was in accordance with the conclusions and guidelines reported previously 10,15,41. Additionally pimavanserin provided robust proof for clinically significant efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…Mild adverse effects such as somnolence, dizziness, headache, weight gain, and orthostasis were more common in quetiapine groups 22,45. Regardless of the conflicting data from the clinical trials showing that quetiapine is effective in addressing PDPsy, quetiapine is currently the most widely prescribed medication in the United States for the treatment of PDPsy 10,2629. Therefore, quetiapine and olanzapine should not be considered as first-line agents due to their side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both studies, patients were withdrawn during the study due to reported adverse effects of neutropenia [ 42 , 48 , 76 , 77 , 78 , 79 , 80 , 81 ]. Although clozapine has shown efficacy in both studies, due to its safety profile and frequent monitoring of blood samples required, other antipsychotic drugs are preferred over clozapine [ 78 , 79 ].…”
Section: Management Of Parkinson’s Disease and Its Associated Psychosismentioning
confidence: 99%
“…However, in both studies, patients were withdrawn during the study due to reported adverse effects of neutropenia [ 42 , 48 , 76 , 77 , 78 , 79 , 80 , 81 ]. Although clozapine has shown efficacy in both studies, due to its safety profile and frequent monitoring of blood samples required, other antipsychotic drugs are preferred over clozapine [ 78 , 79 ]. However, in a meta-analysis performed by Helge Frieling et al in determining the most efficient neuroleptic medication has found out that clozapine can be explicitly recommended for PD psychosis care [ 48 , 80 , 82 , 83 ].…”
Section: Management Of Parkinson’s Disease and Its Associated Psychosismentioning
confidence: 99%